2018
DOI: 10.1155/2018/6920213
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Proteomics Analysis Reveals the Effect of Rhubarb in Rats with Ischemic Stroke

Abstract: Background. Rhubarb, a traditional Chinese medicine, promotes viscera and remove blood stasis. Rhubarb is skilled in smoothening meridians, improving blood circulation which exhibits better efficacy on cerebral ischemic stroke. In this study, we aimed to analyze the underlying mechanisms of rhubarb which treated rats of middle cerebral artery occlusion (MCAO) model according to an iTRAQ-based proteomics and bioinformatics analysis. 30 rats were randomly allocated into three groups including sham group (SG), mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Longao [10] modified method was established to establish MCAO cerebral ischemia reperfusion rat model: rats were anesthetized by intraperitoneal injection of 10% chloral hydrate (300 mg/kg). After complete anesthesia, the rats were fixed in the supine position on the operating table.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Longao [10] modified method was established to establish MCAO cerebral ischemia reperfusion rat model: rats were anesthetized by intraperitoneal injection of 10% chloral hydrate (300 mg/kg). After complete anesthesia, the rats were fixed in the supine position on the operating table.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen cerebra were quickly removed and sectioned into 5 mm slices over ice after reperfusion for 6 h [10]. Brain sections were removed and the remaining brain tissue was frozen in liquid nitrogen and stored at -80°C prior to proteomic analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Li j et al [37] reported that rhubarb aglycone reduced thrombolysis-caused brain microvascular basement membrane impairment through decreasing the level of IgG and increasing the level of type IV collagen (CoLIV) and laminin (LN) and then decreased the intracranial hemorrhage ratio and mortality in cerebral ischemia rats. What is more, Xiangping Lin et al [38] found 287 differentially expression proteins (DEPs) and 76 overlapping DEPs between model group (MG) versus sham group (SG) and rhubarb group (RG) versus MG with iTRAQ-based proteomics analysis. There were 14 DEPs related pathways including synaptic vesicle cycle, cGMP-PKG signaling pathway, amyotrophic lateral sclerosis, long-term potentiation, tuberculosis, and so on.…”
Section: Neuroprotective Effects Of Anthraquinones From Rhubarb Inmentioning
confidence: 99%
“…Ferulic acid exerts a neuroprotective effect in cerebral ischemia through its anti-oxidant and anti-inflammation activity. Koh In addition, proteomics analysis has been used to light on the mechanisms underlying pleiotropic actions of rt-PA [41] and the neuroprotection of traditional Chinese medicines (baicalin [42], Ginkgo biloba extract (EGb761) [43], curcumin [44], Danhong injection [45], quercetin [46], rhubarb [47], hydroxysafflor yellow A [48], Xiao-Xu-Ming decoction [49]), asialoEPO [50], melatonin [51], estradiol [52], PACAP38 [53], tetrandrine [54], simvastatin [55], resveratrol [56], PPARα agonist [57], tetramethylpyrazine nitrone [58], and grape seed extract [59] against ischemic injury).…”
Section: Tissue Proteomics Studies In Animal Ischemia Model With Intementioning
confidence: 99%